Taxonomia e distribuição de Eupatorieae (Asteraceae) no Ceará, nordeste do Brasil - Rebouças, Natanael Costa (2021)
The Eupatorieae tribe comprises approximately 2,200 species, belonging to 182 genera in 19 subtribes, distributed mainly in the Neotropical region. In Brazil, 615 species and 86 genera are registered in all regions and phytogeographic domains. Eupatorieae species are recognized by capitulum discoid, flowers bisexual, corolla never yellow, style branches with long sterile appendage, papillose and cypselae blackened with phytomelanin. This present study had as objective to carry out the survey and taxonomic treatment of Eupatorieae species in Ceará, Northeast Brazil. The state of Ceará comprises an area with different vegetation types, varying according to rainfall and altitudinal factors. Four field expeditions were carried out. The specimens were collected and herborized according to the usual methodology in taxonomy and deposited at the EAC Herbarium. Visits were made to the national herbaria ALCB, EAC and IPA, and borrowed material from the collections HST, HVASF, PEUFR, TANG and TEPB, and consultation of virtual images of the specimens deposited on specialized sites. The identifications were checked based on specialized bibliographies, type materials and protologues. As a result, 33 species and 18 genera were confirmed for the territory of Ceará, with a new record for the Northeast region (Chromolaena mucronata), seven new records in Ceará (Barrosoa betoniciformis, Chromolaena maximilianii, Chromolaena myriocephala, Koanophyllon tinctorium, Mikania glomerata, Mikania jeffreyi and Mikania trinervis) and one species is reiterated as endemic to the state (Piqueriella brasiliensis). The most representative genera in the state are Chromolaena (5 spp.) and Mikania (10 spp.). In Ceará, 88% of Eupatorieae were registered mainly in mountainous areas, from humid to sub-humid climate, with high altitude (700–1,200 m) and rainfall reaching up to 1,200 mm, preferably in vegetation of Dense Ombrophylous Forest.